2008
DOI: 10.1007/s11458-008-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of hexagonal close-packed Ni nanoparticles

Abstract: Hexagonal close-packed Ni nanoparticles were synthesized using a heat-treating technique with the precursors prepared by the sol-gel method. The synthesis condition, structure, and morphology of the samples were characterized and analysed by thermogravimetric analysis (TG), differential thermal analysis (DTA), X-ray diffraction (XRD) and transmission electron microscopy (TEM). Results indicate that the hexagonal close packed Ni nanoparticles were synthesized at a heat-treating temperature of 300uC. The cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Intriguingly, when the particle size is reduced to 3.8 nm, a single peak near 44.5 o could be due to either hexagonal closed-packed Ni (011) and fcc Ni (111) peaks together or separately as they are close to 44.5 o . This conjecture is in line with the probability to form hcp on/ near the surface of the particle and/ or the whole of the NPs when all the unit cells lie on the surface only, as hcp phase being less stable thermodynamically than fcc phase [24]. Since they may not be necessarily intermixed, Ni NPs might have a possible formation of its comparatively less stable hcp structure at/ near the surface or the outer shell, and more stable fcc structure at the core.…”
Section: X-ray Diffraction (Xrd) Studysupporting
confidence: 69%
“…Intriguingly, when the particle size is reduced to 3.8 nm, a single peak near 44.5 o could be due to either hexagonal closed-packed Ni (011) and fcc Ni (111) peaks together or separately as they are close to 44.5 o . This conjecture is in line with the probability to form hcp on/ near the surface of the particle and/ or the whole of the NPs when all the unit cells lie on the surface only, as hcp phase being less stable thermodynamically than fcc phase [24]. Since they may not be necessarily intermixed, Ni NPs might have a possible formation of its comparatively less stable hcp structure at/ near the surface or the outer shell, and more stable fcc structure at the core.…”
Section: X-ray Diffraction (Xrd) Studysupporting
confidence: 69%
“…The latter forms only within a specic temperature range (200-325 C). 31 Once hcp-Ni is formed, it is stable at temperatures below 325 C but reverts back to ccp when the temperature is increased above 360 C. [30][31][32] Considering the metastable nature of the hcp phase, it is difficult to obtain by fast growth techniques (i.e. CVD, spray pyrolysis) Ni particles having a well-dened and controllable ccp/hcp ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Polyols have been the preferred dispersion media for such studies. 31 In their work, Tzitzios et al 35 suggested that polyols with a higher molecular weight have elevated boiling points and are more effective in converting the Ni to an hcp structure. In this view, the temperature appears to be the only important process parameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, HCP nanoparticles have been prepared and characterized using various experimental techniques, i.e., thermogravimetric analysis (TGA), differential thermal analysis (DTA), X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), atomic force microscopy (AFM), X-ray diffraction (XRD), etc . For example, hexagonal-close-packed Ni nanoparticles were synthesized using a heat-treating technique with the precursors prepared by the sol–gel method . The phase transformation from a hexagonal-close-packed Ni to a face-centered-cubic Ni structure occurred when the heat-treating temperature was increased.…”
Section: Introductionmentioning
confidence: 99%